PP9 Managing alcohol intoxication in the night-time economy: staff and patient perspectives. Issue 10 (24th September 2019) - Irving, Andy; Allen, Davina; Blake, Joanne; Moore, Simon; Goodacre, Steve
Abstract : Background: Alcohol-related harms arising in the Night-Time Economy (NTE) impose a substantial burden on emergency services (ES) especially ambulance services engaged in both street level care and transportation of acutely intoxicated patients to a hospital Emergency Department (ED). Alcohol Intoxication Management Services (AIMS) are intended as an alternative care pathway for intoxicated patients who would normally use emergency services and are often run by ambulance services in partnership with other agencies. Despite growing policy interest in AIMS as an alternative pathway it is not known what their users think of them nor the experiences of frontline staff engaged in and around AIMS. Methods: As part of a mixed-method study semi-structured interviews were followed by a survey of users recruited from six different AIMS. A parallel ethnographic component used observations and interviews with ambulance staff in two cities with AIMS and one without. Results: Surveys and interviews found AIMs users retrospectively viewed the decision to take them to AIMS favourably and highly rated the care they received, especially the friendly, non-judgemental atmosphere created between ambulance staff and other agents involved in AIMS. A majority of AIMS survey respondents said they would not have called emergency services (85%) or gone to the ED (75.6%). Ethnographic work showed ambulance personnel considered AIMS to have a positive impact on ES, freeing capacity to attend to other emergencies. Ambulance staff without AIMS worked to avoid conveyance to ED but this could result in extended periods risk assessing individuals at street level, which meant they felt unavailable to address other emergency calls. Conclusions: AIMS are viewed very positively by their users and the ambulance staff involved. Findings from surveys, interviews and ethnography suggest that AIMS and EDs are managing different patient groups in different ways, and thus may represent complementary rather than competing alternatives care pathways.